1986
DOI: 10.1083/jcb.103.4.1355
|View full text |Cite
|
Sign up to set email alerts
|

Epidermal growth factor (EGF) promotes phosphorylation at threonine-654 of the EGF receptor: possible role of protein kinase C in homologous regulation of the EGF receptor.

Abstract: Abstract. Treatment of cells with tumor-promoting phorbol diesters, which causes activation of protein kinase C, leads to phosphorylation of the epidermal growth factor (EGF) receptor at threonine-654. Addition of phorbol diesters to intact cells causes inhibition of the EGF-induced tyrosine-protein kinase activity of the EGF receptor and it has been suggested that this effect of phorbol diesters is mediated by the phosphorylation of the receptor by protein kinase C. We measured the activity of protein kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
32
1

Year Published

1987
1987
2001
2001

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 87 publications
(37 citation statements)
references
References 46 publications
(71 reference statements)
2
32
1
Order By: Relevance
“…It has been recently shown that EGF itself promotes the phosphorylation of threonine 654 of its receptor, possibly through the activation of PKC (22,34). In the following experiments, we provide evidence that if PKC has been down regulated by chronic treatment with a phorbol ester (27), the EGF stimulatory effect on tyrosine autophosphorylation of the receptor is enhanced.…”
Section: Kinetics Of Tyrosine Phosphorylation Of Egf Receptor P-tyrsupporting
confidence: 49%
See 1 more Smart Citation
“…It has been recently shown that EGF itself promotes the phosphorylation of threonine 654 of its receptor, possibly through the activation of PKC (22,34). In the following experiments, we provide evidence that if PKC has been down regulated by chronic treatment with a phorbol ester (27), the EGF stimulatory effect on tyrosine autophosphorylation of the receptor is enhanced.…”
Section: Kinetics Of Tyrosine Phosphorylation Of Egf Receptor P-tyrsupporting
confidence: 49%
“…Moreover, it has recently been observed that EGF promotes the phosphorylation of the threonine 654 of its own receptor (22,34), so that the possible role of PKC in homologous feedback regulation of EGF receptor has been suggested.…”
mentioning
confidence: 99%
“…On the basis of these results, we propose that kinase C phosphorylation of Thr-654 provides a negative control mechanism for the regulation of the mitogenic response of cells to EGF. It was reported that in A431 cells EGF induces the phosphorylation of Thr-654 of the EGF receptor probably by activation of kinase C, potentially leading to a negative-feedback reaction to EGF action (28). This information together with the results presented here may provide an explanation for the well-documented inhibitory effect of EGF on A431 cell proliferation.…”
Section: Resultsmentioning
confidence: 50%
“…For example, phosphorylation of serine and threonine residues within the cytoplasmic domains of the insulin (67,68) and epidermal growth factor receptors (69 -75) diminishes their affinity for insulin and epidermal growth factor, respectively. With respect to the epidermal growth factor receptor, these effects mimic those involved in regulation of the receptor by heterologous ligands (76) such as platelet-derived growth factor (77) and those induced through a negative feedback pathway triggered by binding of epidermal growth factor itself (78).…”
Section: Activation Of Pk-c By Elevated Glucose Concentrations Leads mentioning
confidence: 99%